Optimizing Parabolic Through Collectors for Solar Stills: A 2D CFD Parametric Analysis - Mammar Bouhelal; Amar Rouag; Abdelhamid Bouhelal; Yousef Belloufi (International Journal of Energetica)
The thermal efficiency of parabolic trough collectors (PTCs) is influenced by various parameters, including length, diameter, and mass flow rate. This study employs 2D steady-state Computational Fluid Dynamics (CFD) simulations to investigate heat transfer within PTCs and enhance their performance. Exploring diverse PTC designs, involving variations in length (L = 0.5 to 3 m) and diameter (D = 10 to 60 mm), sourced from existing research to optimize desalination system applications. The investigation covers both laminar and turbulent regimes with fully developed flows, examining the effects of Reynolds number and mass flow rate. The results highlight that collector diameter has the most pronounced impact on thermal efficiency, followed by mass flow rate, while the effect of length can be neglected in comparison. A 50% diameter increase leads to over a 60% rise in efficiency for both laminar and turbulent cases, whereas a 60% decrease in mass flow rate corresponds to a 50% enhancement and a 60% improvement in efficiency for both regimes. These findings suggest that an optimal PTC design should prioritize a smaller diameter and lower mass flow rate, with length being of secondary importance and application-specific considerations also playing a pivotal role.